Behind Kelme's Sponsorship: The Role of Perceived Prestige and Bobotoh Involvement in Strengthening Persib Bandung's Brand Equity - Rezka Arya Maulana; May Dedu; Tiara Muthiarsih (International Journal Labs, 2026)
The development of the professional sports industry has encouraged sports clubs to manage brand equity as a strategic asset capable of enhancing competitiveness and organizational value. In this context, sponsorship serves as a marketing instrument that can strengthen a club’s brand equity through the transfer of brand image from sponsor to sponsored organization. This study aimed to analyze the effect of Kelme’s sponsorship on Persib Bandung’s brand equity, focusing on the role of perceived prestige as a mediating variable and Bobotoh engagement as a moderating variable. The study adopted a quantitative approach using a purposive sampling technique involving 100 Bobotoh who met the research criteria. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that Kelme’s perceived sponsorship brand equity did not have a direct effect on Persib Bandung’s brand equity. However, perceived prestige significantly mediated the relationship between Kelme’s sponsorship brand equity and Persib Bandung’s brand equity. In addition, Bobotoh engagement did not moderate the relationship between Kelme’s sponsorship brand equity and Persib Bandung’s perceived prestige, but it did strengthen the relationship between Kelme’s sponsorship brand equity and Persib Bandung’s brand equity. These findings indicate that improving club brand equity through sponsorship is more effective when it operates through the formation of perceived club prestige, while supporter engagement plays a reinforcing role in enhancing the impact of sponsorship-based brand image transfer.